2020
DOI: 10.1080/13696998.2020.1830286
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Lutetium [177Lu] oxodotreotide versus best supportive care with octreotide in patients with midgut neuroendocrine tumors in France

Abstract: Background and aims: In France, there are approximately 2,400 new cases of neuroendocrine tumors (NETs) annually. Peptide receptor radionuclide therapy with 177 Lu-Dotatate plus long-acting repeatable [LAR] octreotide 30 mg has been shown to significantly improve progression-free survival and overall survival relative to high-dose octreotide LAR 60 mg in patients with unresectable or metastatic progressive midgut NETs. A long-term cost-effectiveness analysis was performed to assess whether 177 Lu-Dotatate is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Using three separate datasets, we have shown that the HRQoL of GEP-NET patients treated with 177 Lu-DOTA-TATE may at least remain maintained for a substantial period following treatment. The effectiveness and cost effectiveness of 177 Lu-DOTATATE have been widely recognised by several HTA agencies [29,30]. We believe our work adds to the existing body of evidence for the effectiveness of 177 Lu-DOTATATE based on the results presented for the GStT study.…”
Section: Discussionmentioning
confidence: 65%
“…Using three separate datasets, we have shown that the HRQoL of GEP-NET patients treated with 177 Lu-DOTA-TATE may at least remain maintained for a substantial period following treatment. The effectiveness and cost effectiveness of 177 Lu-DOTATATE have been widely recognised by several HTA agencies [29,30]. We believe our work adds to the existing body of evidence for the effectiveness of 177 Lu-DOTATATE based on the results presented for the GStT study.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, at each stage along the care pathway, cost-efficiency can be maximised through a comprehensive understanding of the patient population, health system capacity and resources, as well as the most appropriate diagnostic tools, treatments and supportive care interventions. There is some evidence of the cost-effectiveness of specific treatments for NENs, 94,95,[131][132][133][134][135][136][137] and cost-efficiency of care pathways for other conditions has been demonstrated. [13][14][15][16][17][18] It is important to note, however, that there is currently insufficient evidence on the costeffectiveness of many types of NEN management.…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses have shown that RLT is a cost-effective alternative to systemic treatment in other cancers such as neuroendocrine tumors. [25][26][27][28] In the diagnostic process, the proPSMA trial has shown the superior diagnostic value of 68 Ga-PSMA-PET compared with conventional imaging in patients with prostate cancer, and it has also proved to be less costly. 29 Besides primary staging, the early detection of metastasis also has a high value in recurrent disease, such as in the setting of oligometastatic disease 30 and in differentiating nonmetastatic from metastatic prostate cancer.…”
Section: Discussionmentioning
confidence: 99%